The Pedagogical Implication of the Daily Spoken English in the Cinderella (2015) Movie: a Speech Act Discourse Analysis in English Language Education - Ariyanto, Sugeng (English Education Study Program, 2016)
This research was intended to discuss the pedagogical implication of the daily spoken English in a movie. The research design was qualitative and descriptive discourse analysis. The research data were collected through the documentary study of the movie entitled Cinderella (2015). The data were analyzed by using Austin’s speech act theory; the locutionary act, illocutionary act, and perlocutionary act. The research results showed that the characters in Cinderella movie mostly used indirect speech act namely expositives illocutionary acts. Such research findings implied that in English education EFL students should learn the illocutionary forces of English as the target language used in the classroom. They should also know that every utterance has three layers of meanings namely the locutionary act, illocutionary act, and perlocutionary act. Keywords: Discourse Analysis, Speech Act, Spoken Discourse, Movie